2020
DOI: 10.3390/ijerph17072548
|View full text |Cite
|
Sign up to set email alerts
|

Individual, Family, and Environmental Correlates of Motor Competence in Young Children: Regression Model Analysis of Data Obtained from Two Motor Tests

Abstract: Physical activity and motor competence (MC) have been considered to be closely related and prevent childhood obesity. The aim of the study was two-fold: to examine MC measured with two different tools in relation to individual, family, and environmental correlates and to investigate gender differences in MC. The Test of Gross Motor Development-Third Edition (TGMD-3) was administered to three- to seven-year-old children (n = 945), while the Körperkoordinationstest für Kinder (KTK) was also used for five- to sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 60 publications
1
24
0
3
Order By: Relevance
“…Numerous factors influence MC development besides behavioral factors (sedentary time, intensity-specific physical activity, and type of organized sports activities), and, hence, mediate MC effect on the SAG. Niemistö et al [ 54 ] found that the MC levels (model fit = 38%) assessed using the KTK in preschool children significantly depend on biological factors (biological maturation, gender, and temperament traits), participation in organized sports, as well as parents’ education level. We did not find gender as a significant predictor of the MQ variables, although their study showed a significantly higher mean MC in boys and higher mean score for balance test item in girls.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors influence MC development besides behavioral factors (sedentary time, intensity-specific physical activity, and type of organized sports activities), and, hence, mediate MC effect on the SAG. Niemistö et al [ 54 ] found that the MC levels (model fit = 38%) assessed using the KTK in preschool children significantly depend on biological factors (biological maturation, gender, and temperament traits), participation in organized sports, as well as parents’ education level. We did not find gender as a significant predictor of the MQ variables, although their study showed a significantly higher mean MC in boys and higher mean score for balance test item in girls.…”
Section: Discussionmentioning
confidence: 99%
“…This fact has led several authors to try to identify variables that can explain this change that is occurring in the practice of sports activity among adolescents [8][9][10]. In this respect, research has highlighted both individual and contextual factors, responsible for explaining the establishment of sport attitudes and habits [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that having low levels of AMC and PMC does not necessarily prevent children from taking part in organized sports, which is in contrast with previous literature [ 5 , 10 , 33 ]. On the other hand, the expected positive effect in the other direction, with more OSP being associated with higher levels of AMC [ 57 ] and PMC [ 58 ] also seems to be absent in Profile 4. One explanation may be that children in this “low–low–high” profile are supported by their environment to participate in organized sports without necessarily having high levels of AMC or PMC.…”
Section: Discussionmentioning
confidence: 98%